Osteoradionecrosis after Radiation Therapy for Head and Neck Cancer: Differentiation from Recurrent Disease with CT and PET/CT Imaging - Alhilali, L.; Reynolds, A.R.; Fakhran, S. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Our aim was to compare the CT and PET/CT imaging features of osteoradionecrosis with those of recurrent disease after treatment of head and neck malignancy. MATERIALS AND METHODS: We retrospectively reviewed maxillofacial and neck CT scans obtained for suspected osteoradionecrosis or tumor recurrence for the presence of the following: 1) discrete solid mass, 2) cystic mass, 3) interruption of the bony cortex, 4) bony fragmentation, 5) bony trabecular loss, 6) intraosseous gas, and 7) bony sclerosis. Trabecular bone loss was further categorized as permeative (<75% loss of trabecula) or lucent (>75% loss). PET/CT studies performed for suspected osteoradionecrosis or tumor recurrence were evaluated for mean standard uptake value and maximum standard uptake value. RESULTS: Ten maxillofacial CT, 53 neck CT, and 23 PET/CT studies were performed in 63 patients. Osteoradionecrosis was diagnosed by pathology or imaging stability in 46 patients, and tumor recurrence, in 17 patients. Bony sclerosis was found to be significantly more prevalent in osteoradionecrosis and was never seen with tumor recurrence (P = .013). Patients with tumor recurrence were more likely to have a solid (P < .001) or cystic mass (P = .025), which was rare in osteoradionecrosis. While patients with tumor recurrence had significantly higher mean standard uptake values and maximum standard uptake values, there was significant overlap in mean standard uptake values and maximum standard uptake values between the 2 groups. CONCLUSIONS: There is significant overlap of standard uptake values in patients with osteoradionecrosis and tumor recurrence. CT findings provide more reliable diagnostic tools, with a solid or cystic mass strongly associated with tumor recurrence and bony sclerosis seen only with osteoradionecrosis. ORNosteoradionecrosisSUVstandard uptake valueSUVmeanmean standard uptake valueSUVmaxmaximum standard uptake value